Synthesis and Biological Evaluation of Imidazopyridine–Oxindole Conjugates as Microtubule‐Targeting Agents. Issue 12 (23rd September 2013) - Kamal, Ahmed; Reddy, Vangala Santhosh; Karnewar, Santosh; Chourasiya, Sumit S.; Shaik, Anver Basha; Kumar, G. Bharath; Kishor, Chandan; Reddy, M. Kashi; Narasimha Rao, M. P.; Nagabhushana, Ananthamurthy; Ramakrishna, Kallaganti V. S.; Addlagatta, Anthony; et al.
Abstract A library of imidazopyridine–oxindole conjugates was synthesised and investigated for anticancer activity against various human cancer cell lines. Some of the tested compounds, such as 10 a, 10 e, 10 f, and 10 k, exhibited promising antiproliferative activity with GI50 values ranging from 0.17 to 9.31 μM. Flow cytometric analysis showed that MCF‐7 cells treated by these compounds arrested in the G2/M phase of the cell cycle in a concentration‐dependent manner. More particularly, compound 10 f displayed a remarkable inhibitory effect on tubulin polymerisation. All the compounds depolarised mitochondrial membrane potential and caused apoptosis. These results are further supported by the decreased phosphorylation of Akt at Ser473. Studies on embryonic development revealed that the lead compounds 10 f and 10 k caused delay in the development of zebra fish embryos. Docking of compound 10 f with tubulin protein suggested that the imidazo[1, 2‐a]pyridine moiety occupies the colchicine binding site of tubulin.